Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T20:05:56+01:00
A) 2x-11y=73/:
3x-4y=47

x - 5,5y = 36,5
3x-4y=47

x=5,5y + 36,5
3 (5,5y +36,5) - 4y = 47


x=5,5y + 36,5
16,5y + 109,5 - 4y = 47


x=5,5y + 36,5
12,5y = 47- 109,5

x=5,5y + 36,5
12,5y = -62,5/:12,5

x=5,5y + 36,5
y = -5

x=5,5 * (-5) + 36,5
y= -5

x = 9
y = 5


b) -2x+5y=-10 /-2
7x-4y=8

x - 2,5y = 5
7x-4y=8

x = 5 + 2,5y
7(-5 + 2,5y) - 4y = 8

x = 5 + 2,5y
35 + 17,5y - 4y =8

x = 5 + 2,5y
13,5y = - 27/ :13,5y

x = 5 + 2,5y
y = (-2)

x = 0
y = (-2)


c) 9x+8y=1
5x-6y=11/ :5

9x+8y=1
x -1,2y = 2,2

9x+8y=1
x = 1,2y +2,2

9 (1,2y + 2,2) + 8y = 1
x = 1,2y +2,2

10,8y + 19,8 + 8y = 1
x = 1,2y +2,2

18,8y = -18,8 /:18,8
x = 1,2y +2,2

y = -1
x = 1,2 * (-1) +2,2

y = -1
x = 1

2010-02-23T20:33:28+01:00
A)
2x-11y=73
3x-4y=47
2x=73-11y /2
3x-4y=47
x=⁷³/²-¹¹/₂y
3(⁷³/²-¹¹/₂y)-4y=47
x=⁷³/²-¹¹/₂y
²¹⁹/₂+³³/₂y-4y=47
x=⁷³/²-¹¹/₂y
²⁵/₂y=47-²¹⁹/₂
x=⁷³/²-¹¹/₂y
²⁵/₂y=¹²⁵/₂ /(²⁵/₂)
x=⁷³/₂-¹¹/₂y
y=5
x=⁷³/₂-¹¹/₂(2)
y=5
x=⁷³/₂-11
y=5
x=⁵¹/₂

b)
-2x+5y=-10
7x-4y=8
-2x=-10-5y /(-2)
7x-4y=8
x=5+⁵/₂y
7(5+⁵/₂y)-4y=8
x=5+⁵/₂y
35+³⁵/₂y-⁸/₂y=8
x=5+⁵/₂y
²⁷/₂y=8-35 /(²⁷/₂)
x=5+⁵/₂y
y=-27ײ/₂₇
x=5+⁵/₂y
y=-2
x=5+⁵/₂(-2)
y=-2
x=5-5
y=-2
x=0

c)
9x+8y=1
5x-6y=11
9x=1-8y /9
5x-6y=11
x=¹/₉-⁸/₉y
5(¹/₉-⁸/₉y)-6y=11
x=¹/₉-⁸/₉y
⁵/₉-⁴⁰/₉y-⁵⁴/₉y=11
x=¹/₉-⁸/₉y
-⁹⁴/₉y=11-⁵/₉ /(-⁹⁴/₉)
x=¹/₉-⁸/₉y
y=⁹⁴/₉×(-⁹/₉₄)
x=¹/₉-⁸/₉y
y=-1
x=¹/₉-⁸/₉(-1)
y=-1
x=1